Comparação de metodologias para detecção da resistência à meticilina em Staphylococcus aureus - Gindri, Lívia (2013)
Staphylococcus aureus is considered as a microorganism belonging to the normal flora of humans, being both a settler as an infectious pathogen Methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a major cause of nosocomial infections and community. The large increase in resistance to antimicrobials has limited therapeutic options. Thus the proper conduct of testing the susceptibility to drugs is vital to ensure the proper treatment of these infections, and the use of methods capable of detecting resistance quickly and accurately, it is essential in clinical diagnosis . The aim of this study was to compare manual and automated phenotypic methods with genotypic based on Polymerase Chain Reaction (PCR) to detect MRSA strains. A total of 139 samples of S. aureus were analyzed using automated and manual methods phenotypic and compared with the determination of the mecA gene by PCR. A total of 139 samples, 37 (26.6 %) had the gene searched. The oxacillin had a sensitivity of 62.2% and specificity of 95.1 %, while cefoxitin disk for these parameters were 67.6% and 94.1 %, respectively. The automated method was the one that had the highest percentages of sensitivity (67,6 %) and specificity (96.1 %). Some differences were observed when comparing the phenotypic methods with PCR. A combination of methods can be considered as an efficient alternative for the diagnosis of infections caused by MRSA.